The Cell Walls of Green Algae: A Journey through Evolution and Diversity - Domozych, David; Ciancia, Marina; Fangel, Jonatan U.; Mikkelsen, Maria D.; Ulvskov, Peter; Willats, William G. (Frontiers in Plant Science, 2012)
The green algae represent a large group of morphologically diverse photosynthetic eukaryotes that occupy virtually every photic habitat on the planet. The extracellular coverings of green algae including cell walls are also diverse. A recent surge of research in green algal cell walls fueled by new emerging technologies has revealed new and critical insight concerning these coverings. For example, the late divergent taxa of the Charophycean Green Algae possess cell walls containing assemblages of polymers with notable similarity to the cellulose, pectins, hemicelluloses, arabinogalactan proteins, extensin and lignin present in embryophyte walls. Ulvophycean seaweeds have cell wall components whose most abundant fibrillar constituents may change from cellulose to β-mannans to β-xylans and during different life cycle phases. Likewise, these algae produce complex sulfated polysaccharides, arabinogalactan proteins and extensin. Chlorophycean green algae produce a wide array of walls ranging from cellulose-pectin complexes to ones made of hydroxyproline-rich glycoproteins. Larger and more detailed surveys of the green algal taxa including incorporation of emerging genomic and transcriptomic data are required in order to more fully resolve evolutionary trends within the green algae and in relationship with higher plants as well as potential applications of wall components in the food and pharmaceutical industries.